2013
DOI: 10.1523/jneurosci.1400-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Endogenous Opioid Functional Measures in Chronic Back Pain

Abstract: The absence of consistent end organ abnormalities in many chronic pain syndromes has led to a search for maladaptive CNS mechanisms that may explain their clinical presentations and course. Here, we addressed the role of brain regional -opioid receptor-mediated neurotransmission, one of the best recognized mechanisms of pain regulation, in chronic back pain in human subjects. We compared -opioid receptor availability in vivo at baseline, during pain expectation, and with moderate levels of sustained pain in 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 62 publications
(26 reference statements)
1
58
0
Order By: Relevance
“…The fMRI-PET activations overlapping in the medial thalamic sub-region, which has been reported previously for pain induced opioid release (Scott et al, 2007). The thalamus is important for sensory discrimination, transmission/modulation of painful stimuli, and is also a key structure associated with chronic pain development (Tracey and Bushnell, 2009) and pathology of different chronic pain conditions (Martikainen et al, 2013). An earlier study showed that opioid receptor activation (as measured by changes in BP ND ) in the thalamus is associated with sensory and affective response attenuation to sustained pain (Zubieta et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The fMRI-PET activations overlapping in the medial thalamic sub-region, which has been reported previously for pain induced opioid release (Scott et al, 2007). The thalamus is important for sensory discrimination, transmission/modulation of painful stimuli, and is also a key structure associated with chronic pain development (Tracey and Bushnell, 2009) and pathology of different chronic pain conditions (Martikainen et al, 2013). An earlier study showed that opioid receptor activation (as measured by changes in BP ND ) in the thalamus is associated with sensory and affective response attenuation to sustained pain (Zubieta et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Whether there would be correspondence across the acute and chronic pain contexts was unclear, given conflicting findings regarding the impact of chronic pain on endogenous opioid function. [7][8][9] If findings for chronic pain were consistent with findings for brief evoked pain outcomes, 6 we expected that greater endogenous opioid inhibition of chronic pain intensity would be associated with smaller acute analgesic effects of morphine on chronic pain intensity.…”
mentioning
confidence: 87%
“…The latter spatial shift seems to occur even though these subjects judge their back pain as essentially unchanged over the one-year monitoring period. Thus, it seems that chronification of pain, accompanied by gray matter and functional connectivity reorganization, and also accompanied with reduced capacity to activate central opioid neurotransmission (Martikainen et al, 2013), renders the pain to become more subjective/intrapersonal and more emotional.…”
Section: Perception Related Brain Activity In Chronic Painmentioning
confidence: 99%